The effect of special exercises in the development of some biochemical and physical variables on the technical performance of the shooting skill from the corner for handball players (Journal of the College of Basic Education, 2023)
Modern technical means have contributed to helping researchers, scholars, and those in charge of the teaching process in the field of physical education to change and bypass the old means and methods dependent on them and take them out of the realm of speculation and approval to adopt modern scientific methods. Appropriate training methods and methods, adopting mechanistic theories in training and applying them in the field to obtain the most appropriate motor paths, which lead to improving sports technique. Every sports event requires that the athlete possess levels of strength, speed, and some physical capabilities. Since the training methods and programs have a role in determining the physical and physiological capabilities to evaluate the sports performance during the various stages of training for the purpose of detecting strengths and weaknesses and avoiding errors that occur in the engineering path with an itinerary. the movement . In order to reach a solution to the duty of movement in the best economic way and the implementation of skillful performance under biomechanical conditions so that it does not go beyond the framework of laws and regulations for the required effectiveness. From a fundamental impact on the outcome of the match, which requires skill, agility, and high technical performance, which depends on a lot of kinematic and physical variables, which requires us to research them continuously to diagnose and develop them through field training. For the skill of shooting from the corner, and this importance comes as a result of the difficulty of penetration from the corner, in order to obtain a positive result that contributes to the performance of the skills of the handball game.